Embedded instrumentation system for optical tomography based on image sensor - Ab. Ghani, Mohd. Amir Hamzah (2014)
Tomography technique was used widely for its visualisation by section ability. The technique that is popularly used in process industry has high efficiency and is able to improve manufacturing sector. Optical tomography can capture images of objects moving in high speed is a convenience and commonly used in process industry particularly in chemical process. Optical tomography system can be embedded with a controlling unit capable of giving instructions in which to operate the optical sensors. The embedded controlling unit helps reduce processing time of data collection and can be conveniently placed in a minimal working space environment. The main component for the embedded optical tomographic system is the Charge Coupled Device (CCD) used as an image sensor. The SONY ILX551A CCD sensor that has 2048 effective pixels was placed outside of a pipe on an octagon shape Perspex due to its non-intrusive nature. There are four projections used for the tomography system with a single CCD sensor placed at each end of the projection. The CCD sensors are controlled by an embedded system including an ATMEGA1284P microcontroller that produces driving signals needed to turn on the four CCDs in the system. The microcontroller Timer function generates the signal according to the sequence needed by the CCD sensors. The speed of the data produced correlates with the speed of the timing signals sent out from the microcontroller. The experimental result recorded was based on the four conditions: when the sensors were fully open, fully closed, half open and when an object is present. The image of when an object present condition was produced through image processing method. Hence, the embedded instrumentation system for optical tomography based on image sensors manages to obtain data accordingly to the sensors detection.